![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Nhận xét: \(x-1< x+4\)
=> \(\hept{\begin{cases}x-1< 0\\x+4>0\end{cases}}\Rightarrow-4< x< 1\)
b) Nếu: \(\hept{\begin{cases}x>0\\4-x>0\end{cases}}\Rightarrow0< x< 4\)
Nếu: \(\hept{\begin{cases}x< 0\\4-x< 0\end{cases}}\Rightarrow∄x\)
c) Nếu: \(\hept{\begin{cases}1-3x>0\\8+x< 0\end{cases}}\Rightarrow x< -8\)
Nếu: \(\hept{\begin{cases}1-3x< 0\\8+x>0\end{cases}\Rightarrow}x>\frac{1}{3}\)
d) Nếu: \(\hept{\begin{cases}2x+6>0\\4-x>0\end{cases}}\Rightarrow-3< x< 4\)
Nếu: \(\hept{\begin{cases}2x+6< 0\\4-x< 0\end{cases}}\Rightarrow∄x\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có : \(\dfrac{\left(x-3\right)\left(x+2\right)\left(x+1\right)}{\left(x+3\right)\left(x-4\right)}>0\)
- Đặt \(f\left(x\right)=\dfrac{\left(x-3\right)\left(x+2\right)\left(x+1\right)}{\left(x+3\right)\left(x-4\right)}\)
- Lập bảng xét dấu :
- Từ bảng xét dấu : - Để f(x) > 0
\(\Leftrightarrow\left[{}\begin{matrix}-3< x< -2\\-1< x< 3\\x>4\end{matrix}\right.\)
Vậy ...
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(\left(5x-1\right)\left(2x-\frac{1}{3}\right)=0\)
\(\Rightarrow\orbr{\begin{cases}5x-1=0\\2x-\frac{1}{3}=0\end{cases}\Rightarrow}\orbr{\begin{cases}5x=1\\2x=\frac{1}{3}\end{cases}\Rightarrow}\orbr{\begin{cases}x=\frac{1}{5}\\x=\frac{1}{6}\end{cases}}\)
b. \(\left(x^2+1\right)\left(x-4\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x^2+1=0\\x-4=0\end{cases}\Rightarrow}\orbr{\begin{cases}x^2=-1\left(Voly\right)\\x=4\end{cases}\Rightarrow x=4}\)
c, \(2x^2-\frac{1}{3}x=0\)
\(\Leftrightarrow x\left(2x-\frac{1}{3}\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\2x-\frac{1}{3}=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=0\\x=\frac{1}{6}\end{cases}}\)
d, \(\left(\frac{4}{5}\right)^{5x}=\left(\frac{4}{5}\right)^7\)
\(\Rightarrow5x=7\)
\(\Rightarrow x=\frac{7}{5}\)
e, Ta có: \(A=\frac{x+5}{x-2}=\frac{\left(x-2\right)+7}{x-2}=1+\frac{7}{x-2}\)
Để A ∈ Z <=> (x - 2) ∈ Ư(7) = { ±1; ±7 }
x - 2 | 1 | -1 | 7 | -7 |
x | 3 | 1 | 9 | -5 |
Vậy....
a) \(\left(5x-1\right)\left(2x-\frac{1}{3}\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}5x-1=0\\2x-\frac{1}{3}=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}5x=1\\2x=\frac{1}{3}\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{5}\\x=\frac{1}{6}\end{cases}}\)
Vậy : ....
b) \(\left(x^2+1\right)\left(x-4\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x^2+1=0\\x-4=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x^2=-1\left(loại\right)\\x=4\end{cases}}\)
c) \(2x^2-\frac{1}{3}x=0\)
\(\Leftrightarrow x\left(2x-\frac{1}{3}\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\2x-\frac{1}{3}=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x=\frac{1}{6}\end{cases}}\)
Vậy :...
x = 0 + 1/4
x = 1/4